A revision of Pheidole Westwood (Hymenoptera: Formicidae) in the islands of the Southwest Indian Ocean and designation of a neotype for the invasive Pheidole megacephala - Fischer, G.; Fisher, B. L. (Zootaxa, 2013)
The myrmicine genus Pheidole Westwood is revised for the smaller islands of the Southwest Indian Ocean: Comoros, Juan de Nova Island, Mauritius, Mayotte, Réunion, and the Seychelles. Descriptions and keys are provided for the thirteen spe-cies on these islands of which seven are newly described: P. decepticon sp. n., P. dodo sp. n., P. komori sp. n, P. loki sp. n., P. megatron sp. n., P. ragnax sp. n., P. vulcan sp. n.; and six were previously described: P. braueri Forel, P. fervens Smith, F., P. jonas Forel, P. megacephala (Fabricius), P. parva Forel, and P. teneriffana Forel. New synonymies (with the senior synonym listed first) include P. parva Mayr = P. flavens var. farquharensis Forel, P. parva Mayr = P. tarda Don-isthorpe, P. megacephala (Fabricius) = P. picata Forel, P. megacephala (Fabricius) = P. punctulata r. gietleni Forel, 1905, P. megacephala (Fabricius) = P. picata var. bernhardae Emery, 1915, P. megacephala (Fabricius) = P. megacephala r. scabrior Forel, and P. teneriffana Forel = P. voeltzkowii Forel. Furthermore, lectotypes are designated from the syntypes of P. braueri, P. fervens, P. jonas, P. parva, and P. teneriffana in order to provide a single name-bearing specimen and to facilitate future taxonomic studies. Finally, a neotype is provided for the untraceable or possibly lost type of the cosmo-politan and invasive P. megacephala, which was originally described by Fabricius from Mauritius (the former ‘Ile de France’).